The Role of Corporate Social Responsibility Disclosure in Improving Financial Performance (Case study in Indonesian Islamic Bank) - Mukhibad, Hasan; Muthmainah, Muthmainah; Andraeny, Dita (Universitas Negeri Surabaya, 2020)
The influence of social care by business entities to their financial performance has been continuously debated in previous management reseearch. Nevertheless, studies about the influence of CSR on Islamic banks financial performance were rarely done. Therefore, this studyaims to examine the influence of Corporate Social Responsibility Disclosure (CSRD) on profitability as measured by Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM) and Investment Account Holders (IAH) by debt and financing ratio. Data was obtained from Islamic banks in Indonesia through observation from 2012 to 2018 that analyzed by panel data regression and Fixed Effect Model (FEM). The results showed that the CSRD did not have a positive influence on ROA, ROE, NPM, IAH, Debt, and Financing Ratio. Therefore, the legitimacy theory was not proven in this study.